A gestão de processos como um meio para a gestão de documentos: a atuação do profissional arquivista na construção de um núcleo de planejamento e controle de processos e documentos - Flavia de Melo Lacerda (2019)
The objective of this work is to present and analyze how process management can be a facilitator for achieving document management, through the building of the Planning and Control Center of processes and normative documents produced at the Rede Batista de Educação. The institution is presented in its historical and administrative context, as well as the NPC implementation project. The participation of the institution's archivist at the core construction stages is presented through the detailing of their work during the project stages. Process management is presented as an alternative ally to document management. The methodology used comprises interviews and theoretical foundation of Archivology.The archivist's work in each of these steps is analyzed in the eye of the Archive Management theories and Administration theories. At the end, this dissertation presents the application of the project results in the archiving reality of the Rede Batista de Educação.